Legal Certainty and the Enforceability of Marriage Agreements on Marital Property - R. Febrina Andarina Zaharnika (JURNAL AKTA, 2026)
A marriage agreement, or huwelijksche voorwaarden, is a legal instrument recognized under Article 29 of Law No. 1 of 1974 concerning Marriage and reinforced by the Constitutional Court Decision Number 69/PUU-XIII/2015. This agreement serves to regulate the separation of assets between husband and wife while at the same time providing legal certainty for the parties involved. However, in practice, marriage agreements often raise legal issues, particularly regarding their consequences for joint property as well as individual property. This study aims to analyze the legal consequences of marriage agreements through a case study of Pekanbaru District Court Decision No. 68/PDT/G/2009/PN.PBR Jo No. 62/PDT.G/2015/PN.PBR, in connection with the principle of legal certainty. The research method applied is normative juridical, employing statutory, doctrinal, and case study approaches. The findings reveal that although marriage agreements are legally valid, their implementation continues to face challenges, especially in relation to the enforcement of legal certainty. This study emphasizes the necessity for harmonization of legal norms and consistency in judicial decisions in order to ensure that marriage agreements have binding legal force in protecting the interests of the parties.